Predictors of posttraumatic growth in women with breast cancer. Issue 12 (18th October 2013) - Danhauer, Suzanne C.; Case, L. Douglas; Tedeschi, Richard; Russell, Greg; Vishnevsky, Tanya; Triplett, Kelli; Ip, Edward H.; Avis, Nancy E.
Abstract Objective Posttraumatic growth (PTG) is defined as 'positive psychological change experienced as a result of a struggle with highly challenging life circumstances'. The current study examined change in PTG over 2 years following breast cancer diagnosis and variables associated with PTG over time. Methods Women recently diagnosed with breast cancer completed surveys within 8 months of diagnosis and 6, 12, and 18 months later. Linear mixed effects models were used to assess the longitudinal effects of demographic, medical, and psychosocial variables on PTG as measured by the Posttraumatic Growth Inventory (PTGI). Results A total of 653 women were accrued (mean age = 54.9, SD = 12.6). Total PTGI score increased over time mostly within the first few months following diagnosis. In the longitudinal model, greater PTGI scores were associated with education level, longer time since diagnosis, greater baseline level of illness intrusiveness, and increases in social support, spirituality, use of active–adaptive coping strategies, and mental health. Findings for the PTGI domains were similar to those for the total score except for the Spiritual Change domain. Conclusion PTG develops relatively soon after a breast cancer diagnosis and is associated with baseline illness intrusiveness and increases in social support, spirituality, use of active–adaptive coping strategies, and mental health. Copyright © 2013 John Wiley & Sons, Ltd.